Emerging Role of m6 A Methylome in Brain Development: Implications for Neurological Disorders and Potential Treatment - Sokpor, Godwin; Xie, Yuanbin; Nguyen, Huu P.; Tuoc, Tran (Frontiers in Cell and Developmental Biology, 2021)
Dynamic modification of RNA affords proximal regulation of gene expression triggered by non-genomic or environmental changes. One such epitranscriptomic alteration in RNA metabolism is the installation of a methyl group on adenosine (m6A) known to be the most prevalent modified state of mRNA in the mammalian cell. The methylation machinery responsible for the dynamic deposition and recognition of m6A on mRNA is composed of subunits that play specific roles, including reading, writing and erasing of m6A marks on mRNA to influence gene expression. As a result, peculiar cellular perturbations have been linked to dysregulation of components of the mRNA methylation machinery or its cofactors. It is increasingly clear that neural tissues/cells, especially in the brain, make the most of m6A modification in maintaining normal morphology and function. Neurons in particular display dynamic distribution of m6A marks during development and in adulthood. Interestingly, such dynamic m6A patterns are responsive to external cues and experience. Specific disturbances in the neural m6A landscape lead to anomalous phenotypes, including aberrant stem/progenitor cell proliferation and differentiation, defective cell fate choices, and abnormal synaptogenesis. Such m6A-linked neural perturbations may singularly or together have implications for syndromic or non-syndromic neurological diseases, given that most RNAs in the brain are enriched with m6A tags. Here, we review the current perspectives on the m6A machinery and function, its role in brain development and possible association with brain disorders, and the prospects of applying the CRISPR-dCas13b system to obviate m6A-related neurological anomalies.